2020
DOI: 10.3390/ijerph17155454
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cancer Chronic Pain Conditions and Risk for Incident Alzheimer’s Disease and Related Dementias in Community-Dwelling Older Adults: A Population-Based Retrospective Cohort Study of United States Medicare Beneficiaries, 2001–2013

Abstract: Accumulating evidence suggests that certain chronic pain conditions may increase risk for incident Alzheimer’s disease and related dementias (ADRD). Rigorous longitudinal research remains relatively sparse, and the relation of overall chronic pain condition burden to ADRD risk remains little studied, as has the potential mediating role of sleep and mood disorders. In this retrospective cohort study, we investigated the association of common non-cancer chronic pain conditions (NCPC) at baseline to subsequent ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 81 publications
2
26
2
1
Order By: Relevance
“…Due to potential pharmacodynamic interaction between muscarinic antagonists and acetylcholinesterase inhibitors (AChEIs), AD patients with asthma/COPD might benefit more from memantine than AChEIs [ 53 , 56 ]. Osteoarthritis or other chronic non-cancer pain is associated with an elevated risk of AD-related dementia; this association is particularly pronounced in those with osteoarthritis and pain, and mood disorders may partially mediate this relationship [ 57 , 58 ]. Although studies have emphasized the importance of pain control for AD patients, pain management is still a dilemma because of the side-effects of opioids.…”
Section: Comprehensive Ad Managementmentioning
confidence: 99%
“…Due to potential pharmacodynamic interaction between muscarinic antagonists and acetylcholinesterase inhibitors (AChEIs), AD patients with asthma/COPD might benefit more from memantine than AChEIs [ 53 , 56 ]. Osteoarthritis or other chronic non-cancer pain is associated with an elevated risk of AD-related dementia; this association is particularly pronounced in those with osteoarthritis and pain, and mood disorders may partially mediate this relationship [ 57 , 58 ]. Although studies have emphasized the importance of pain control for AD patients, pain management is still a dilemma because of the side-effects of opioids.…”
Section: Comprehensive Ad Managementmentioning
confidence: 99%
“…Consistent with our findings, this study documented a strong, positive, dose–response association of perceived memory loss to osteoarthritis and associated joint pain, an association that appeared mediated in part by sleep and mood impairment. Likewise, published research regarding the collective and incremental relation of common NCPCs to incident ADRD remains sparse, to date limited to our recent study in a large sample of US elders enrolled in fee-for-service Medicare (Khalid et al, 2020). In this prior investigation, we found risk of ADRD to rise significantly with increasing number of pain conditions at baseline after adjusting for sociodemographic, lifestyle and comorbid conditions, and medication use (Khalid et al, 2020), with risk estimates similar overall to those observed in the current study of WV elders.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence from experimental (Moriarty et al, 2011; Cao et al, 2019) and cross-sectional (Van Der Leeuw et al, 2015; Ikram et al, 2019) studies suggests significant neurocognitive impairment, including deterioration in attention, memory, and executive function with chronic pain and certain NCPCs, as well as adverse neurostructural and neurofunctional changes paralleling those implicated in ADRD pathogenesis (Ng et al, 2018; Cao et al, 2019). Longitudinal studies from North America (Whitlock et al, 2017; van der Leeuw et al, 2018; Ezzati et al, 2019; Khalid et al, 2020), Europe (Veronese et al, 2018), and East Asia (Yang et al, 2016; Tzeng et al, 2018; Yamada et al, 2019) also suggest significant associations of chronic pain and certain NCPCs to subsequent deterioration in memory (Whitlock et al, 2017; van der Leeuw et al, 2018), accelerated cognitive decline (Whitlock et al, 2017), new onset cognitive impairment (Whitlock et al, 2017; van der Leeuw et al, 2018), and incident ADRD (Ezzati et al, 2019; Innes & Sambamoorthi, 2020; Khalid et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5 Em paralelo, a dor crônica é um grave problema porque tem uma alta prevalência, e gera uma incapacidade física e emocional nos indivíduos. 83 Nesta perspectiva, as evidências sugerem que a dor crônica pode aumentar o risco de declínio cognitivo e demência, 92,93 assim como consiste em um fator de risco para a morte prematura. 86 O conhecimento sobre a epidemiologia da dor ainda é escasso, principalmente, no que diz respeito ao nível socioeconômico.…”
Section: Proposiçõesunclassified